Teaching STEM outdoors : activities for young children - Selly, Patty Born (St. Paul, MN Redleaf Press, 2017)
"Connect nature play, outdoor experiences, and STEM learning for young children with activities, real-life examples, and educator resources. Nurture young children's innate tendencies toward exploration, sensory stimulation, and STEM learning when you connect outdoor learning and STEM curriculum. Discover the developmental benefits of outdoor learning and how the rich diversity of settings and materials of nature gives rise to questions and inquiry for deeper learning. Full of activities, examples, and resources to take the fun of STEM outside, this book will help teachers articulate connections between nature play, outdoor experiences, and STEM learning in young children. Use STEM and nature-based learning to nurture children's curiosity and exploration of the world. Patty Born Selly is an assistant professor of environmental education and STEM at Hamline University. She previously served as the executive director of the National Center for STEM Elementary Education at St. Catherine University. Selly has over twenty years of experience in early childhood education, has written two books, and regularly consults other educators on science and nature education approaches for young children"--
"Research shows that an increasing number of early care and education providers want to take children outdoors more often and see real value in nature-based learning. This book will help them articulate connections between nature play, outdoor experiences, and STEM learning in young children. The book will include activities, examples, and resources for readers"--
An increasing number of early care and education providers want to take children outdoors more often and see real value in nature-based learning. Selly helps articulate connections between nature play, outdoor experiences, and STEM learning in young children. The book includes activities, examples, and resources for readers.
Foreword / by David Sobel -- Introduction -- What is STEM? -- Why kids need nature -- An overview of the STEM disciplines -- Building on a strong STEM foundation -- Putting it all together -- STEM starts.
Includes bibliographical references.
105902
Keywords: Science -- Study and teaching (Early childhood) -- Activity programs; Outdoor education; Education. -- Preschool & Kindergarten; Education. -- Curricula; Education. -- Teaching Methods & Materials -- Science & Technology; Education. -- Elementary; STEM education